ANALISIS PELAKSANAAN PAK DALAM KELUARGA UNTUK MENUMBUHKAN IMAN ANAK USIA 6-9 TAHUN DI HKBP RESSORT HUTARAJA KEC. SIPOHOLON TAHUN 2019 - venny bertha gultom (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
Keywords: Implementation Of PAK In The Family, Grow The Child’s FaithThis study aims to determine how much the level of implementation of PAK in the family to grow the immunity of shildren aged 6-9 years at HKBP Ressort Hutaraja District Sipoholon in 2019. Quantitative methods, with a population of shildren aged 6-9 years at HKBP Ressort Hutaraja District Sipoholon as many as 58 people. The research instrument was as closed questionnaire. The questionnaire trial was conducted for 30 children aged 6-9 year at the HKI Pagarbatu Ressort Pagarbatu Ressort Tarutung Utara Region II Silindung. After the questionnaire was tested, it was know that the rxy value af each item was between 0,377-0,555 which means rtable (0,361) so that the research instrument was reliable and could be used as a research instrument.